Nightshift : a novel - Ladner, Kiare (Mariner Books, 2022)
"A haunting, compelling debut novel of complex female friendship and obsession, following one young woman's decision to abandon her normal life and join the otherworldly, nocturnal existence of London's nightshift workers"--